2021
DOI: 10.3390/atoms9040089
|View full text |Cite
|
Sign up to set email alerts
|

BAl4Mg−/0/+: Global Minima with a Planar Tetracoordinate or Hypercoordinate Boron Atom

Abstract: We have explored the chemical space of BAl4Mg−/0/+ for the first time and theoretically characterized several isomers with interesting bonding patterns. We have used chemical intuition and a cluster building method based on the tabu-search algorithm implemented in the Python program for aggregation and reaction (PyAR) to obtain the maximum number of possible stationary points. The global minimum geometries for the anion (1a) and cation (1c) contain a planar tetracoordinate boron (ptB) atom, whereas the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 108 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…S14, ESI †). A similar geometry involving a p/s dual aromatic planar-pentacoordinate B (ppB) was reported recently, where one of the Al is replaced by Mg. 98 BAl 4 has a kite-like structure with a planar tetra coordinate boron (ptB) at the center.…”
Section: Boron-aluminummentioning
confidence: 99%
“…S14, ESI †). A similar geometry involving a p/s dual aromatic planar-pentacoordinate B (ppB) was reported recently, where one of the Al is replaced by Mg. 98 BAl 4 has a kite-like structure with a planar tetra coordinate boron (ptB) at the center.…”
Section: Boron-aluminummentioning
confidence: 99%
“…34 Recently, Khatun et al studied the PES of BAl 4 Mg À/0/+ systems and found that the anionic and cationic states of the system have planar tetracoordinate boron (ptB) and the neutral state has a ppB atom in the global minima. 35 The ptB and the ppB structures were reported as kinetically stable and exhibit p/s double aromaticity. In 2001, Minkin and coworkers designed BB 6 (CH) 3 and BB 6 X 2 À (X = NH and O) systems having a planar hexacoordinate boron (phB) atom at both ab initio and DFT level computations.…”
Section: Introductionmentioning
confidence: 99%
“…39 However, this approach is computationally quite expensive for larger elemental compositions like C 12 O 2 Mg 2 . Of course, from our previous studies of small clusters such as CAl 4 Mg −/0 64 and BAl 4 Mg −/0/+ , 65 we realized that it does not guarantee all possible low-lying isomers although global minimum can be found unequivocally.…”
Section: Resultsmentioning
confidence: 92%
“…Another strategy developed by some of the authors is to build the molecules bottom-up starting from a single atom by adding the remaining atoms sequentially searching for local minima at each stage and using those minima to grow the molecule up to the desired composition. 39 However, this approach is computationally quite expensive for larger elemental Of course, from our previous studies of small clusters such as CAl 4 Mg À/064 and BAl 4 Mg À/0/+ , 65 we realized that it does not guarantee all possible low-lying isomers although global minimum can be found unequivocally.…”
Section: Why Chemical Intuition Is Necessary?mentioning
confidence: 99%